2022
DOI: 10.3390/microorganisms10122356
|View full text |Cite
|
Sign up to set email alerts
|

CD36—A Host Receptor Necessary for Malaria Parasites to Establish and Maintain Infection

Abstract: Plasmodium falciparum-infected erythrocytes (PfIEs) present P. falciparum erythrocyte membrane protein 1 proteins (PfEMP1s) on the cell surface, via which they cytoadhere to various endothelial cell receptors (ECRs) on the walls of human blood vessels. This prevents the parasite from passing through the spleen, which would lead to its elimination. Each P. falciparum isolate has about 60 different PfEMP1s acting as ligands, and at least 24 ECRs have been identified as interaction partners. Interestingly, in eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 143 publications
0
12
0
3
Order By: Relevance
“…Our previous work and others have shown that host-parasite interactions at the vascular endothelial interface are mediated by and/or result in up- or down-regulation of key vascular endothelial adhesion molecules such as ICAM1, ICAM2, CD36, E- and P-selectin, ESAM, VCAM1 and PECAM1. We selected the adhesion molecules to analyze based on their previously studied relevance to Trypanosoma infections (De Niz et al, 2021; Girard et al, 2005; Masocha et al, 2007; Silva Pereira et al, 2022) as well as other protozoan parasites (Bachmann et al, 2022; Cunningham et al, 2017; De Niz et al, 2016; Hopp et al, 2015; Ross et al, 2021). We used intravital imaging and fluorescence microscopy to quantify how the expression of key endothelial cell adhesion molecules changed upon infection, focusing on the first peak of parasitemia of each Trypanosoma species.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work and others have shown that host-parasite interactions at the vascular endothelial interface are mediated by and/or result in up- or down-regulation of key vascular endothelial adhesion molecules such as ICAM1, ICAM2, CD36, E- and P-selectin, ESAM, VCAM1 and PECAM1. We selected the adhesion molecules to analyze based on their previously studied relevance to Trypanosoma infections (De Niz et al, 2021; Girard et al, 2005; Masocha et al, 2007; Silva Pereira et al, 2022) as well as other protozoan parasites (Bachmann et al, 2022; Cunningham et al, 2017; De Niz et al, 2016; Hopp et al, 2015; Ross et al, 2021). We used intravital imaging and fluorescence microscopy to quantify how the expression of key endothelial cell adhesion molecules changed upon infection, focusing on the first peak of parasitemia of each Trypanosoma species.…”
Section: Resultsmentioning
confidence: 99%
“…Sequestration of erythrocytes in micro-vessels has been observed both in malaria and babesiosis [ 257 , 258 ]. This results from a cyto-adhesive phenomenon, and in babesiosis caused by B. bovis, this is partially caused by variant erythrocyte surface antigen 1 (VESA1), while proteins of the P. falciparum erythrocyte membrane protein 1 ( Pf EMP1) family have a role during malaria [ 258 , 259 ]. These proteins act as ligands for receptors on the endothelial cell surface [ 258 , 259 ].…”
Section: Sequestration Of Rbcsmentioning
confidence: 99%
“…This results from a cyto-adhesive phenomenon, and in babesiosis caused by B. bovis, this is partially caused by variant erythrocyte surface antigen 1 (VESA1), while proteins of the P. falciparum erythrocyte membrane protein 1 ( Pf EMP1) family have a role during malaria [ 258 , 259 ]. These proteins act as ligands for receptors on the endothelial cell surface [ 258 , 259 ]. Although other bovine Babesia species such as B. bigemina and B. divergens express VESA proteins (VESA1 or VESA2), Jackson et al [ 260 ] reported that only B. bovis infection leads to cytoadherence of infected RBCs and sequestration of erythrocytes in the microvasculature of cattle [ 260 ].…”
Section: Sequestration Of Rbcsmentioning
confidence: 99%
“…The better characterized ECRs are CD36, EPCR, and intercellular adhesion molecule-1 (ICAM1). CD36 was one of the first described ECRs and has been extensively characterized [ 122 ]. This receptor has also been widely used in the study of cytoadherence.…”
Section: Cytoadherence Receptorsmentioning
confidence: 99%
“…The various alleles of PfEMP1 exhibit different phenotypes in regard to the endothelial cell receptors that they recognize. This cytoadherence phenotype is largely due to the subtypes of DBL and CIDR adhesion domains that make up a specific PfEMP1 allele [ 8 , 20 , 122 ]. In other words, receptor binding is often associated with a single adhesive domain, or a combination of adhesive domains found in domain cassettes ( Table 3 ).…”
Section: Cytoadherence Receptorsmentioning
confidence: 99%